Design Thinking for Social Innovation - and Brown, Tim; Wyatt, Jocelyn (Stanford Social Innovation Review, 2010)
Designers have traditionally focused on enhancing the look and functionality of products. Recently, they have begun using design techniques to tackle more complex problems, such as finding ways to provide low-cost healthcare throughout the world. Businesses were the first to embrace this new approach—called design thinking—and nonprofits are beginning to adopt it too.